The Use of Circle Games to improve the Mastery of English Vocabulary of the Indonesian Maritime Academy Students - Nur Aeni; Fitriani Fitriani; Nur Fitri (Universitas Negeri Makassar, 2019)
The research's aim was to find out if the use of circle games substantially enhances the vocabulary competence of the learners and to find out whether or not the learners are interested in using circle games. The study used a quasi-experimental technique. The study population was AMI AIPI Makassar's first year students in the academic year 2018/2019. The sample consisted of 50 students in Technical Class A and B. The research used cluster random sampling. In AMI AIPI Makassar, the investigator took two classes of the first year Technical Class students. The classes were split into the experimental class and class control. The results showed an important distinction between the score of the learners taught using circle games and without Circle Games. It was demonstrated by the experimental class ' mean score, which in the posttest was greater than the control class. The test outcome showed that the use of Circle Games substantially increased the mastery of the students. Analysis using the Likert Scale showed that learners wanted to learn English through Circle Games.